2019
DOI: 10.1002/smll.201902998
|View full text |Cite
|
Sign up to set email alerts
|

Sequentially Site‐Specific Delivery of Apoptotic Protein and Tumor‐Suppressor Gene for Combination Cancer Therapy

Abstract: Nanocarrier‐mediated codelivery of multiple anticancer drugs is a potential strategy for enhanced efficacy of combination cancer treatment by unifying differential pharmacokinetic properties and maintaining an optimal ratio of drug cargoes. However, a programmable codelivery system is highly desired to deliver different therapeutics to their specific sites of action to pursue maximized combinational effect. Herein a liposome‐based nanoassembly (p53/C‐rNC/L‐FA) is developed for intracellular site‐specific deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 58 publications
1
27
0
Order By: Relevance
“…In some cases, to increase the transfection efficacy, DNA-liposome therapy is combined with other mechanic procedures like ultrasounds [22]. Chen and collaborators designed a liposome-based nanoconjugate (p53/C-rNC/L-FA) for site-specific intracellular delivery of an apoptotic protein cytochrome c and a plasmid DNA encoding tumor-suppressing p53 protein [207]. The authors demonstrated that p53/C-rNC/L-FA liposome induce apoptosis in tumor cell lines and inhibited tumor growth in a breast cancer mouse model [207].…”
Section: Lipid Basedmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, to increase the transfection efficacy, DNA-liposome therapy is combined with other mechanic procedures like ultrasounds [22]. Chen and collaborators designed a liposome-based nanoconjugate (p53/C-rNC/L-FA) for site-specific intracellular delivery of an apoptotic protein cytochrome c and a plasmid DNA encoding tumor-suppressing p53 protein [207]. The authors demonstrated that p53/C-rNC/L-FA liposome induce apoptosis in tumor cell lines and inhibited tumor growth in a breast cancer mouse model [207].…”
Section: Lipid Basedmentioning
confidence: 99%
“…Chen and collaborators designed a liposome-based nanoconjugate (p53/C-rNC/L-FA) for site-specific intracellular delivery of an apoptotic protein cytochrome c and a plasmid DNA encoding tumor-suppressing p53 protein [207]. The authors demonstrated that p53/C-rNC/L-FA liposome induce apoptosis in tumor cell lines and inhibited tumor growth in a breast cancer mouse model [207]. Zuo and collaborators also used liposomes to deliver p53 but in this case for ovarian cancer targeted therapy [208].…”
Section: Lipid Basedmentioning
confidence: 99%
“…The enhanced vectorization potential and intrinsic tumor cytotoxicity of OVs were also exploited to transiently express tumor suppressors at high levels but still lack clinical assessment [129]. Regarding nanoparticles, liposomes containing p53-encoding plasmids are being evaluated against different types of solid cancers [219,220], including in phase I/II clinical trials (NCT02354547, NCT02340156, NCT02340117).…”
Section: Gene Therapymentioning
confidence: 99%
“…Similar approaches using ctyC as the model protein have also been undertaken employing DNA-mediated membrane fusion [110] or pH dependent fusion. [111] In some cases, codelivery systems were employed which provided maximized combinational effects, and have been shown to be more effective in preclinical and clinical studies. [112,113]…”
Section: Peptide-mediated Membrane Fusion With Liposomesmentioning
confidence: 99%